The Social Construction of Financial Accountability in Government and Parliament Discourses - Seyed Mojtaba Shafipoor; GhanbarAli Rajabloo; Kaveh Mehrani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Differences in the perceptions of various social groups, including parliamentarians, government officials, and elites from financial accountability, raise the question of what the meaning of financial accountability is or how it is understood. So, with a post-structuralist approach, we considered financial accountability as a social construct, and we get a better understanding of it from Norman Fairclough's theoretical knowledge of text analysis, and Laclau and Mouffe in the context of political discourse analysis. We analyzed the parliament's detailed negotiations on the adoption of the budget of the entire country in the deliberations of the government and the parliament and classified the research findings in the six political, economic and social paradigms of Iran after the revolution. The findings of the research, summarized briefly in this article, indicate the influence of power relations and the use of hegemonic elements in the discourse system formed in the discourses of the government and the parliament. Thus, in each paradigm, dominant discourses formed with context, and by highlighting themselves and marginalizing rival discourse, they succeeded in securing a temporary centralized sign and a new articulation of the semantic system of financial accountability.